Reality of remote Training in light of the Corona pandemic from the male and female teacher's point of view at Riyadh and Dammam - Al-Shaye, Abdullah Mohmmad; Al-Wadey, Afnan Ali Mohmmad (Journal of Educational and Psychological Sciences, 2023)
This study addresses the reality of remote training in light of the Corona pandemic from the male and female teacher's point of view at Riyadh and Dammam. The study used the descriptive methodology to achieve the study objectives using the survey too to disclose reality of remote training in light of the Corona pandemic l. The study was applied to a sample of (223) male and female teachers. The data analysis revealed the following findings: The study sample of male and female teachers at Riyadh and Dammam believe that remote training in light of the Corona pandemic is highly practiced, while the most targeted programs are: (the training programs concerned with the modern developments in the technical field in addition to the training programs the modern developments in the educational field). There is a neutral endorsement by the study sample of male and female teachers regarding the remote training obstacles in light of the Corona pandemic, while the most remote training obstacles from their point of view are (The excessive teaching burdens and the frequent works and responsibilities related to the family and others). There are no statistically significant differences between the study sample members regarding the following variables (gender, experience years, educational qualification and the place of work). According to the above mentioned findings, the two researchers recommend the following: reducing the teaching burdens for the male and female teachers to enable them to join the remote training programs. The researchers also recommend that attracting human trainers competencies and providing maintenance and programming specialists for repairing malfunctions that may occur during remote training. In addition, providing the male and female teachers with financial and moral incentives to encourage them to join these remote training programs.
Keywords: Corona pandemic; remote training